Effect of pregnancy on the course of immune thrombocytopenia: a retrospective study of 118 pregnancies in 82 women. (24th June 2014) - Loustau, Valentine; Debouverie, Odile; Canoui‐Poitrine, Florence; Baili, Lilia; Khellaf, Mehdi; Touboul, Claudine; Languille, Laetitia; Loustau, Marine; Bierling, Philippe; Haddad, Bassam; Godeau, Bertrand; Pourrat, Olivier; et al.
Summary In women with pre‐existing immune thrombocytopenic purpura (ITP), the effect of pregnancy on the course of the disease is poorly known. We performed a dual‐centre retrospective cohort study of 118 pregnancies in 82 women with primary ITP. In early pregnancy, the platelet count was <100 × 109/l in 35·6% of pregnancies. During pregnancy the median platelet count nadir was 66 × 109/l (25th–75th percentile: 42–117), with platelet count <30 × 109/l for 26 pregnancies (22%). In 49% of pregnancies, a significant decrease of the platelet count required treatment at least transiently in preparation for delivery. At the time of delivery, the median platelet count was 110 × 109/l (77–155). Compared to before pregnancy, at 3 months post‐partum, only 11% of pregnancies [95% confidence interval (95% CI): 6·8–20·2] showed disease worsening. Previous splenectomy was the only factor significantly associated with ITP worsening after pregnancy (53·9% vs. 10·3%, P < 0·001). For 8·3% of the pregnancies (95% CI: 3·8–15·1), neonatal thrombocytopenia required treatment, especially in case of previous maternal splenectomy (adjusted odds ratio 16·7, 95% CI: 2·61–106). The overall risk of exacerbation of ITP and severe thrombocytopenia during pregnancy is acceptable.